Transfer Money Policy through Credit Channels in Vietnam - An, Pham Thi Ha; Dung, Nguyen Thi Quynh (International Journal of Economics and Financial Issues, 2019)
Study and examines the impact of monetary policy transmission through credit channels in Vietnam based on the research model of Sun et al. (2010). To estimate this model system, the author uses VECM method with secondary data taken from reliable sources on the situation of Vietnam consumer price index, credit growth of the economy, deposits of customers, industrial production in Vietnam, growth of M2 money supply, rediscount interest rate; VN Index from January 2008 to December 2017. The research results show that both in the short and long-term, the rediscount rate has a negative impact on the credit growth of the economy. When the State Bank of Vietnam implements an expansionary monetary policy with a discounted interest rate tool, it will have an impact on increasing the total credit supply of the economy. However, an increase in economic credit will increase economic output ( represented by Vietnam’s industrial production value) in the short term; or the impact of monetary policy transmission via credit channel in Vietnam shows that there exists a short-term credit channel but does not exist in the long term. Keywords: monetary policy, credit channels, VECM method JEL Classifications: E5, E52, E51 DOI: https://doi.org/10.32479/ijefi.8752